Studi Komparasi Strategi Numbered Head Together (NHT) dan Strategi Team Game Tournament (TGT) Terhadap Hasil Belajar Mata Pelajaran Ipa Kelas III SD Muhammadiyah 4 Kandangsapi Tahun 2015/2016 - Andriyanto, Dika (2016)
This study aims to determine: (1) differences in the effect of the strategy and the strategy Numbered Head Together Team Game Tournament on learning natural Sciences third grade students of SD Muhammadiyah Surakarta 4 Kandangsapi Year 2015/2016. (2) a better strategy between strategy and strategy Numbered Head Together Team Game Tournament on learning outcomes natural Sciences third grade students of SD Muhammadiyah Surakarta 4 Kandangsapi Year 2015/2016. This study included a quantitative study with an experimental model, the research subjects graders IIIA and IIIB 4 Kandangsapi SD Muhammadiyah Surakarta. The data collection technique using the techniques of tests and documentation. Test instrument is used to test the validity and reliability testing. Data were analyzed using t-test technique which preceded the prerequisite test analysis, the test of normality and homogeneity test. Based on data analysis with a significance level of 5% was obtained t_hitung> t_tabel, namely 2.104> 2.012. And obtained a mean value between grade classes are taught using Numbered Head Together strategy and classes are taught using the strategy of Team Game Tournament 75.84> 67.67. The conclusion of this study were (1) there is a difference between the effects of Numbered Head Together and strategy Team Game Tournament on learning outcomes natural Sciences third grade students of SD Muhammadiyah Surakarta 4 Kandangsapi Year 2015/2016. (2) Team Game Tournament strategies are better than Numbered Head Together on learning outcomes natural Sciences third grade students of SD Muhammadiyah Surakarta 4 Kandangsapi Year 2015/2016.